Productivity Measurement of Shoes Production Using Objective Matrix and The Improvement Effort (Case Study at PT XYZ) - Ratna Dewi, Prihatini; Nusraningrum, Dewi (International Humanities and Applied Science Journal, 2020)
PT XYZ is the shoes manufacturer in Tangerang that produces Mizuno and Specs brand. Many competitors in the shoes industry enforce the company to improve all aspects; one of them is to improve the problem of low productivity achievement in Mizuno production line. This study aims to know the productivity measurement method by using Objective matrix, and to do analysis of productivity criteria that dominantly contribute to the low productivity in Mizuno production line. This research method was using Objective Matrix (OMAX), Pareto diagram, Fishbone diagram, and 5W1H. Base on the result, it was identified that the highest productivity performance indicator was happened in August 2018 and the lowest productivity performance indicator was happened in March 2018. While for productivity index, the lowest productivity index was happened in March 2018 and the highest productivity index was happened in April 2018. Criteria that dominantly contributed to the decreased productivity in Mizuno production line was on criteria 1 (utilization of material usage), criteria 6 (number of loss output / down time), and criteria 2 (labor utilization), therefore the focus for improvement in this research was to prioritize these criteria to gain increased productivity in Mizuno production line.